PENGEMBANGAN MEDIA PEMBELAJARAN SEA AND LAND DALAM MENINGKATKAN KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN - Marciana Pasaribu; Meta Br Ginting (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2019)
The purpose of this research is to improve the numeracy skills of children aged 5-6 years at TK Kartika 1-23 Medan Helvetia through the Development of Sea and Land Media. This research is a development research. The subject in this study were all children of group B Kindergarten Insan Pandhega, amount of8 children (as a small group) and all children of group B of Jeruk TK Kartika 1-23 Medan Helvetia, amount of 20 children (as a large group). Data collection techniques were carried out by giving questionnaires to the team of practitioners and academics to determine the level of eligibility of Sea and Land media and observations to determine the effectiveness of Sea and Land Media in increasing children's numeracy skills. Based on the results of data collection, it was obtained the level of eligibility of Sea and Land media is 92.3%, so that the Sea and Land Media is very appropriate to use. The results of data collection through observation sheets, the average of substraction ability of small groups when pre-test was 37.5%. increase to 95.8% in the post-test and the average of addition ability when pre-test was 50%, increased to 95.8% in the post-test. Based on the results of the analysis of large groups of data the average ability to substract for children when pre-test was 35%, an increase of 96.7% in the post-test. The average of addition number of children when pre-test 41.7%, increased to 96.7% in the post-test. It was concluded that Media Sea and Land was effective in increasing the numeracy skill of children aged 5-6 years. Abstrak Tujuan penelitian ini adalah untuk meningkatkan kemampuan berhitung anak usia 5-6 tahun di TK Kartika 1-23 Medan Helvetia melalui Pengembangan Media Sea and Land. Penelitian ini adalah penelitian pengembangan. Subjek penelitian ini adalah seluruh anak kelompok B TK Insan Pandhega yang berjumlah 8 anak (sebagai kelompok kecil) dan seluruh anak kelompok B Jeruk TK Kartika 1-23 Medan Helvetia yang berjumlah 20 anak (sebagai kelompok besar). Teknik pengumpulan data dilakukan dengan cara pemberian angket kepada tim praktisi dan akademisi untuk mengetahui tingkat kelayakan media Sea and Land dan observasi untuk mengetahui tingkat keefektifitas Media Sea and Land dalam meningkatkan kemampuan Berhitung anak. Berdasarkan hasil pengumpulan data diperoleh nilai tingkat kelayakan media Sea and Land 92,3%, Media Sea and Land sangat layak digunakan. Hasil pengumpulan data melalui lembar observasi,rata-rata kemampuan pengurangan kelompok kecil ketika pre-test 37,5%, meningkat 95,8% pada post-test. Rata-rata kemampuan penjumlahan kelompok kecilketika pre-test 50%,meningkat menjadi 95,8% pada post-test. Berdasarkan hasil analisis data kelompok besar rata-rata kemampuan pengurangan anak ketika pre-test 35% , meningkat 96,7% pada post-test. Rata-rata kemampuanpenjumlahan anak pada kelompok besar ketika pre-test 41,7%, meningkat menjadi 96,7% pada post-test.Disimpulkan bahwa Media Sea and Land efektif meningkatkan kemampuan berhitung anak usia 5-6 tahun. Kata Kunci: media, kemampuan berhitung,penjumlahan, pengurangan